(untitled) (Journal of Engineering, 2016)
Galvanic corrosion of stainless steel 316 (SS316) and carbon steel (CS) coupled in 5% wt/v sulfuric acid solution at agitation velocity was investigated. The galvanic behavior of coupled metals was also studied using zero resistance ammeter (ZRA) method. The effects of agitation velocity, temperature, and time on galvanic corrosion current and loss in weight of both metals in both free corrosion and galvanic corrosion were investigated. The trends of open circuit potential (OCP) of each metal and galvanic potential (Eg) of the couple were, also, determined. Results showed that SS316 was cathodic relative to CS in galvanic couple and its OCP was much more positive than that of CS for all investigated ranges of operating conditions. A sharp increase in galvanic current from CS to SS316 was noticed in the first 20 min and then decrease with time. Increasing the agitation velocity led to increase in galvanic corrosion rate. The decrease in galvanic current is attributed to metal passivation due to the formation of a protective film which grows with time. The minus sign in galvanic current means that the current is flow from CS (anode) to SS316 (cathode). The galvanic current of CS-SS316 couple shifts to the negative direction with increase agitation velocity.